Vilfredo Pareto. Manual of Political Economy - Arthmar, Rogério (Estudos Econômicos (São Paulo), 2015)
Resenha bibliográficaVilfredo Pareto. Manual of Political Economy. A critical and variorum edition. Edited by Aldo Montesano, Alberto Zanni, Luigino Bruni, John Chipman and Michael McLure. Oxford: Oxford University Press, 2014, 664 p.